Lens Opacity and Hydrogen Sulfide in a New Zealand Geothermal Area. Issue 4 (April 2017) - Bates, Michael N.; Bailey, Ian L.; DiMartino, Robert B.; Pope, Karl; Crane, Julian; Garrett, Nick
ABSTRACT: Purpose: Hydrogen sulfide (H2 S) is a highly toxic gas with well-established, acute irritation effects on the eye. The population of Rotorua, New Zealand, sited on an active geothermal field, has some of the highest ambient H2 S exposures in the world. Evidence from ecological studies in Rotorua has suggested that H2 S is associated with cataract. The purpose of the present study was, using more detailed exposure characterization, clinical examinations, and anterior eye photography, to more directly investigate this previously reported association. Methods: Enrolled were 1637 adults, ages 18 to 65, from a comprehensive Rotorua primary care medical register. Patients underwent a comprehensive ophthalmic examination, including pupillary dilation and lens photography to capture evidence of any nuclear opacity, nuclear color, and cortical and posterior subcapsular opacity. Photographs were scored for all four outcomes on the LOCS III scale with decimalized interpolation between the exemplars. H2 S exposure for up to the last 30 years was estimated based on networks of passive samplers set out across Rotorua and knowledge of residential, workplace, and school locations over the 30 years. Data analysis using linear and logistic regression examined associations between the degree of opacification and nuclear color or cataract (defined as a LOCS III score ≥2.0) in relation to H2 S exposure. Results: No associations were found between estimated H2 S exposures and any of the four ophthalmic outcome measures. Conclusions: Overall, results were generally reassuring. They provided no evidence that H2 S exposure at the levels found in Rotorua is associated with cataract. The previously found association between cataract and H2 S exposure in the Rotorua population seems likely to be attributable to the limitations of the ecological study design. These results cannot rule out the possibility of an association with cataract at higher levels of H2 S exposure.